Collected writings of John Maynard Keynes Vol XXVII- Activities 1940-1946 Shaping the post-war world employment and commodities - Moggridge, Donald (Ed.); Keynes, John Maynard (Cambridge Cambridge University Press, 2013)
Surplus, relief and commodity policy